Enhancing quality of medical care in low income and middle income countries through simulation-based initiatives: recommendations of the Simnovate Global Health Domain Group. (24th March 2017) - Puri, Lekha; Das, Jishnu; Pai, Madhukar; Agrawal, Priya; Fitzgerald, J Edward; Kelley, Edward; Kesler, Sarah; Mate, Kedar; Mohanan, Manoj; Okrainec, Allan; Aggarwal, Rajesh
Abstract : Background: Quality of medical care in low income and middle income countries (LMICs) is variable, resulting in significant medical errors and adverse patient outcomes. Integration of simulation-based training and assessment may be considered to enhance quality of patient care in LMICs. The aim of this study was to consider the role of simulation in LMICs, to directly impact health professions education, measurement and assessment. Methods: The Simnovate Global Health Domain Group undertook three teleconferences and a direct face-to-face meeting. A scoping review of published studies using simulation in LMICs was performed and, in addition, a detailed survey was sent to the World Directory of Medical Schools and selected known simulation centres in LMICs. Results: Studies in LMICs employed low-tech manikins, standardised patients and procedural simulation methods. Low-technology manikins were the majority simulation method used in medical education (42%), and focused on knowledge and skills outcomes. Compared to HICs, the majority of studies evaluated baseline adherence to guidelines rather than focusing on improving medical knowledge through educational intervention. There were 46 respondents from the survey, representing 21 countries and 28 simulation centres. Within the 28 simulation centres, teachers and trainees were from across all healthcare professions. Discussion: Broad use of simulation is low in LMICs, and the full potential of simulation-based interventions for improved quality of care has yet to be realised. The use of simulation in LMICs could be a potentially untapped area that, if increased and/or improved, could positively impact patient safety and the quality of care.